Homogeneous magnetic flux in Rydberg lattices - J. Eix; R. Bai; T. Lahaye; A. Browaeys; H. P. Büchler; S. Weber (Physical Review Research)
We present a method for generating homogeneous and tunable magnetic flux for bosonic particles in a lattice using Rydberg atoms. Our setup relies on Rydberg excitations hopping through the lattice by dipolar exchange interactions. The magnetic flux arises from complex hopping via ancilla atoms. Remarkably, the total flux within a magnetic unit cell directly depends on the ratio of the number of lattice sites to ancilla atoms, making it topologically protected to small changes in the positions of the atoms. This allows us to optimize the positions of the ancilla atoms to make the flux through the magnetic unit cell homogeneous. With this homogeneous flux, we get a topological band in the single-particle regime. In the many-body regime, we obtain indications of a bosonic fractional Chern insulator state at ν=1/2 filling.